Identifying the Dimensions of the Self-Knowledge Model for Managers in Iranian Public Organizations - Deilami Moezzi, Amid; Mokhtari Bayekolaei, Mehran; Kia Kojouri, Davood (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The objective of this study was to explore and identify the variables and dimensions of the self-awareness model for managers in Iranian public organizations.Methodology: This qualitative research utilized a content analysis approach, drawing upon interviews with experts in the field of public management. A total of 10 managers and specialists in Iranian public organizations participated in semi-structured interviews. Data were coded using open, axial, and selective coding methods. The analysis focused on identifying primary themes and categories related to the self-awareness model.Findings: The content analysis revealed 43 initial codes from 151 interview excerpts, which were categorized into five key themes: (1) Consequences of Self-Awareness, (2) Functional Factors of Self-Awareness, (3) Individual Factors of Self-Awareness, (4) Behavioral Criteria of Self-Awareness, and (5) Self-Awareness Skills. Among these, Behavioral Criteria of Self-Awareness was the most frequently cited theme, followed by Functional Factors of Self-Awareness and Consequences of Self-Awareness. Additionally, 90% of the respondents mentioned the importance of Behavioral Criteria of Self-Awareness, highlighting its significance in the self-awareness model.Conclusion: The findings indicate that self-awareness plays a critical role in enhancing managerial effectiveness and improving performance in public organizations. The study contributes to the development of a comprehensive model of self-awareness for managers, emphasizing both emotional and behavioral aspects. The results underscore the need for managers in Iranian public organizations to focus on self-awareness skills and behavioral criteria to achieve better decision-making, performance, and personal growth. Future research should explore the application of these findings in broader organizational contexts and examine the impact of self-awareness on organizational outcomes.